2015
DOI: 10.3758/s13415-015-0374-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported tolerance influences prefrontal cortex hemodynamics and affective responses

Abstract: The relationship between cognitive and sensory processes in the brain contributes to the regulation of affective responses (pleasure-displeasure). Exercise can be used to manipulate sensory processes (by increasing physiological demand) in order to examine the role of dispositional traits that may influence an individual's ability to cognitively regulate these responses. With the use of near infrared spectroscopy, in this study we examined the influence of self-reported tolerance upon prefrontal cortex (PFC) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 36 publications
4
36
2
Order By: Relevance
“…Our data show similar benefits on the patient's brain. The individual acutely and chronically increased his PFC oxygenation during exercise (see Figure 3), and these metabolism changes are in conformity with previous findings that presented greater brain oxygenation during incremental exercise (Bediz et al, 2016;Chang et al, 2013;Tempest & Parfitt, 2016). Improvements in the oxygen delivered to the PFC can possibly be related to increased number of angiogenic factors due to the exercise program, thus increasing the number of capillaries in the region (Ding et al, 2006;Swain et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data show similar benefits on the patient's brain. The individual acutely and chronically increased his PFC oxygenation during exercise (see Figure 3), and these metabolism changes are in conformity with previous findings that presented greater brain oxygenation during incremental exercise (Bediz et al, 2016;Chang et al, 2013;Tempest & Parfitt, 2016). Improvements in the oxygen delivered to the PFC can possibly be related to increased number of angiogenic factors due to the exercise program, thus increasing the number of capillaries in the region (Ding et al, 2006;Swain et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown the wide range of benefits that exercise promotes on frontal regions of the brain (Hillman, Erickson, & Kramer, 2008;Tempest & Parfitt, 2016), cognition, ANS control and psychosocial aspects (Bahrke & Morgan, 1978;Flausino, Da Silva Prado, de Queiroz, Tufik, & de Mello, 2012). Studies have also suggested aerobic exercise as a possible complementary tool to treat substance use disorder such as alcohol and cocaine Grandjean da Costa et al, 2017;Manthou et al, 2016;Roessler, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These results provide evidence for the theory that the PFC plays a role in interpreting afferent feedback and regulating affect (i.e., pain, displeasure, and fatigue) during fatiguing tasks [ 11 , 15 ]. Negative affect is known to influence exercise tolerance and may play a role in the resulting response to uncomfortable sensations [ 32 ]. Several studies have shown that the amygdala is a key region of convergence for exercise-related interoceptive information [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to this system, the right prefrontal region may indicate prevention (i.e., active avoidance of a negative state) and the left prefrontal region (larger ΔO 2 Hb) may indicate promotion (i.e., completion of the task; Strauman & Wilson, ). However, this system has been shown to activate orbital (Eddington, Dolcos, Cabeza, Krishnan, & Strauman, ) whereas tolerance has been shown to activate dorsal (Tempest & Parfitt, ) regions of the prefrontal cortex. Without qualitative data and a specific research design to test these interpretations, such explanations of the lateralized cognitive and affective processes that occur during exercise remain speculative and are encouraged in appropriately designed future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, those individuals with high self‐reported tolerance potentially indicated a reduced (defensive) motivational state and showed potentially less activity in the amygdala at the most challenging intensities. It is proposed that different cognitive strategies are employed by individuals with a high and low tolerance to combat negative/aversive states during exercise (Tempest & Parfitt, ), yet these remain to be tested. The results reinforce the use of the tolerance scale in exercise testing to help identify individuals susceptible to a negative experience in order to tailor the exercise program to provide a more pleasant and manageable experience (Hall et al, ).…”
Section: Discussionmentioning
confidence: 99%